Influence of Ni and Ti on the Response to Simulated Marine Corrosion of Weathering Steel a242 [Influencia de Ni y Ti en la Respuesta a la Corrosión Marina Simulada de Un Acero Autopatinable a242 - Sipos-Hrabal, K; Bustos-Castillo, O; Monsalve-Gonzalez, A; Artigas-Abuin, A; Allende-Seco, R (Universidade Federal do Rio de Janeiro, 2015)
There is a great interest in the steel industry to incorporate new products in the market with better properties of those already in production. Among these properties, corrosion resistance is of great importance for countries with a large marine seacoast, like Chile, where chloride ions from sea spray produce corrosion, leading to irreversible failure of steel structures decreasing their life. For this reason, it is of vital importance to investigate the influence of various alloying elements and treatments for steels with superior corrosion resistance properties in marine environment. This work aims at studying the specific influence of Nickel - as an alloy constituent - and Titanium - as a microstructural tuner - on ASTM A242 low alloy weathering steel. For that, atmospheric corrosion resistance was evaluated through accelerated salt spray corrosion experiments under wet/dry cycles. For each alloy the thickness of corrosion products and corrosion rates were determined. The oxides and oxyhydroxides were identified by X-Ray diffraction technique. The results showed that corrosion rates at 40 cycles (960 hours) were low for Ni alloyed specimens and even lower for the Ti alloyed specimens, in comparison to the ASTM A242 alloy specimens. These results are reflected in a decrease in the thickness of the corroded coupons, with the lowest value observed for the ASTM A242 steel specimens alloyed with Nickel and Titanium. © 2015, Universidade Federal do Rio de Janeiro. All rights reserved.